MICROSEISMICITY AND SEISMOTECTONIC PROPERTIES OF THE LEFKADA – KEFALONIA SEISMIC ZONE - Karakostas, V. G.; Papadimitriou, E. E.; Karamanos, Ch. K.; Kementzetzidou, D. A. (Bulletin of the Geological Society of Greece, 2010)
Microseismicity, focal–mechanisms, and previously–published focal parameter data are used to determine the current tectonic activity of the prominent zone of seismicity in Lefkada and Kefalonia Islands. Recordings from a local network installed and operated on the two Islands, as well as from permanent stations there, were used to obtain accurate microseismicity locations, which in turn is exploited to reveal properties of smaller localized active structures and the large–scale crustal faulting. The microseismicity substantially agrees with the historic seismicity and delineates a relatively narrow, major zone of activity that extends along the western coasts of both Islands. Cross sections were used in order to provide a detailed characterization of the microseismicity and a high–resolution picture of the seismically defined structures. For the investigation of the past seismic activity relocation of the hypocenters of older events was performed, using a reliable velocity model and time delays for the regional stations, calculated on the basis of the accurately determined focal parameters using the local recordings. The yielding location improvement contributes to the geometry identification of the active structures, which were previously obscured by location errors, and which constitute a critical input for the study area seismic hazard assessment.